Social strategy use and language learning contexts: A case study of Malayalee undergraduate students in India - Sindhu Harish (System, 2014)
This article reports on the social strategy use among India’s Malayalee undergraduate students across eight university colleges in one university in Kerala State. The investigation examines social strategy use in three main language learning contexts (in class, on campus outside the classroom, and off campus) and explores the topic from structuralist and so- ciocultural perspectives. The study also investigates the interplay of stakeholders’ desires and opportunities in conversational contexts, in which individuals and groups deployed social strategies and yet experienced their sociocultural positions being challenged. Data were collected through interviews and the Social Strategy Inventory for Language Learning (SSILL), a questionnaire that was built on but expanded beyond the social strategies in Oxford’s (1990) Strategy Inventory for Language Learning (SILL). Results indicate that although participating Malayalee undergraduate students seem highly motivated and fairly cooperative, they settled for less than optimal use of interactive social strategies, probably because their legitimate right to become proficient speakers of English continued to be hampered by language education policies. The situation is far more pervasive than what several previous studies of language learning strategies (LLS) had envisaged. These findings imply that there is an urgent need to socialize and acculturate the less proficient Malayalee students into English-speaking groups to make their transition from schools to colleges smoother and to give them more autonomy.